Ambiguous Neutrality: Kompas’ Position Amid the Wave of Political Polarization During the Presidential Election 2014 - Wijayanto, Wijayanto (P2KK LIPI, 2018)
This study aims to examine the position of Kompas daily newspaper amid the wave political polarization during Indonesian presidential election 2014 and explain the underlying reason behind it. Based on six months on site observation within the daily’s newsroom as well as content analysis to 278 of Kompas’ article during the presidential campaign, this study found that the actual position of the daily has been ambiguous. On one hand, it claimed to be neutral in its editorial policy, but on the other hand, most of its editorial elites as well as its reporters had personally supported Jokowi. Furthermore, even though the daily has managed to be in a relative balance in term of space in its coverage, it has favored Jokowi in term of tone. This study argues there are political, economy as well as cultural reasons underlying this ambiguous position. Politically, Kompas took position to be neutral to stay close, and to avoid conflict, with whoever might win the election. Economically, this position was taken to maximize its economic interest to maintain its readers whose supports were also divided to the two pairs of candidates and to keep the chance to get advertising revenue from both candidates. Finally, this position has been justified by the shared cultural values among the journalists that this is important to remain neutral to avoid direct confrontation with either Presidential candidate. This values has been embodied as part of the habitus of the journalists which its development primarily took place under the previous authoritarian era. This situation is surprisingly similar with the case in the post authoritarian South American countries, in which the legacy of the authoritarian past still takes hold to the current state of its journalism.